Dynamic and quantity of N losses by volatilization and leaching in Brown Grayish soil of central Cuban region - Juan Almaguer López Código (Universidad Central "Marta Abreu" de Las Villas, 2021)
An experiment was carried out during four harvests (two in the cold season and two in spring) with the objective ofdetermining the N losses by leaching and volatilization as well as their dynamics in a Brown Grayish soil in the Central Cuban region at the Experimental Station of Soil “Escambray” in corn crop. Six N levels were applied (0, 60, 120, 180, 240 y 300 kg ha-1 of N) a third of which with ammonium sulfate when planting and the remaining 35 days with urea. Volatilization of ammonium in form of ammonia was determined using Nömmik’s method in levels 0, 120 and 240 kg ha-1 to 3, 7, 14, 21, 28 and 35 days after fertilization. The washing of NO3- and NH4+ was quantified using a lysimeter type Ebermeyer. Ammonia losses due to volatilization increased along with N doses in the two seasons, reaching its maximum level between the 3rd and 7th days after the second urea fertilization with values of 25 kg ha-1. NH4+ leaching was insignificant. while NO3- losses increased along with the doses and were approximately 13 % of the applied N reaching values of 47 kg ha-1 in the dose of 300 kg ha-1. It is concluded that in Brown Grayish soil the greatest losses due to ammonium volatilization occur with urea and the greatest leaching occurs in NO3-